1996
DOI: 10.1021/ja960429j
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Requirements for β-Hairpin Formation:  Model Studies with Four-Residue Peptides and Depsipeptides

Abstract: Spectroscopic and crystallographic data are presented for a series of tetrapeptides and analogous depsipeptides that can form a minimal β-hairpin (two intramolecular hydrogen bonds). These model compounds have been used to test the hypothesis that "mirror image" β-turns promote β-hairpin formation. This hypothesis was inspired by a statistical survey of β-hairpins in globular proteins (Sibanda, B. L.; Thornton, J. M. Nature 1985, 316, 170), which showed that mirror image β-turns (type I′ and type II′), althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
208
0
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(222 citation statements)
references
References 45 publications
13
208
0
1
Order By: Relevance
“…2) that we have previously shown to adopt a ␤-hairpin conformation in aqueous solution (14,16). D P contains a central D-Pro-Gly segment to induce formation of a ''mirror image'' ␤-turn (type IЈ or IIЈ) (32)(33)(34)(35)(36); the local right-handed twist of such turns is compatible with the right-handed twist of the strands in a ␤-sheet (37). Although D-proline is not a proteinogenic residue, structural analysis of 12-mer D P via two-dimensional NMR shows that this peptide adopts a native-like two-stranded antiparallel ␤-sheet conformation in aqueous solution (14,16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) that we have previously shown to adopt a ␤-hairpin conformation in aqueous solution (14,16). D P contains a central D-Pro-Gly segment to induce formation of a ''mirror image'' ␤-turn (type IЈ or IIЈ) (32)(33)(34)(35)(36); the local right-handed twist of such turns is compatible with the right-handed twist of the strands in a ␤-sheet (37). Although D-proline is not a proteinogenic residue, structural analysis of 12-mer D P via two-dimensional NMR shows that this peptide adopts a native-like two-stranded antiparallel ␤-sheet conformation in aqueous solution (14,16).…”
Section: Resultsmentioning
confidence: 99%
“…Replacing D-Pro with L-Pro completely abolishes ␤-hairpin formation (14,16,18,34,36), and the L-Pro diastereomer of D P provides an excellent representation of the completely unfolded state of D P (i.e., an excellent source of ␦ U values). Closing off the open end of D P with a second D-Pro-Gly segment generates a cyclic peptide, c( D P) 2 , which has a very high ␤-sheet population (i.e., an excellent source of ␦ F values) (16).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the type I + GI P-bulge turns are more prevalent than the type I in P-hairpins, suggesting that the former is more favorable for /?-hairpin formation, as we observe in our designed peptide models. Previous studies indicated that type I turns do not have the proper geometry toward the right-handed twist commonly observed in protein P-sheets (Sibanda & Thornton, 1985;Haque et al, 1994Haque et al, , 1996Haque & Gellman, 1997) and suggest why this type of turn may not be favorable for /?-hairpin formation. The results obtained with our peptide systems are consistent with this suggestion.…”
Section: Comparison Of P-hairpin 4:4 and P-hairpin 3:5 Formationmentioning
confidence: 99%
“…Some peptides containing non-natural amino acids (Haque et al, 1994(Haque et al, , 1996 as well as nonpeptide scaffolds able to bring the two strands together (LaBrenz & Kelly, 1995;Nesloney & Kelly, 1996;Nowick et al, 1996aNowick et al, , 1996b were designed with the purpose of studying P-hairpin formation. However, as far as we know, no stabilizing interstrand side-chain interactions were identified in these model systems.…”
mentioning
confidence: 99%
“…A centrally positioned D-Pro-Gly or D-Pro-Ala segment had been used to facilitate type IIЈ or type IЈ ␤-turn formations (12)(13)(14)(15). Initially the two strands of the ␤-hairpins for which crystals were obtained were composed of all ␣-amino acid residues (16)(17)(18).…”
mentioning
confidence: 99%